Audit of vitamin D deficiency in ethnic pregnant population at Liverpool Womens Hospital. (16th November 2010) - Akhtar, M; Tildesley, R; Cliffe, H; Topping, J
Abstract : Introduction: It is suggested that vitamin D deficiency during pregnancy is associated with increased risk of pre-eclampsia, insulin resistance and gestational diabetes. Experimental data demonstrate that vitamin D is important for fetal development and immunological function. Vitamin D deficiency in pregnancy may impair maternal skeletal preservation and fetal skeletal formation. Moreover, deficiency may affect fetal 'imprinting' increasing susceptibility to chronic disease later in life. Methodology: Retrospective audit of 344 patients for 2007 and 2008. All newly booked ethnic patients who attended LINK (Antenatal clinic for non-English speaking population) at Liverpool Womens Hospital were reviewed. Standard: National Institute for Health and Clinical Excellence (NICE) recommends that vitamin D supplementation may be given to women at greatest risk including women of South Asian, African, Caribbean or Middle Eastern origin. Outcome: Vitamin D levels, calcium levels, pregnancy outcomes and breastfeeding uptake. Vitamin D deficiency all ethnicity Breastfeeding all ethnicity: Conclusion: (1) Majority of women of Asian (not only South Asian), African and Arab countries have severe deficiency of vitamin D. (2) Chinese women presented with moderate vitamin D deficiency, although this group has not been highlighted by NICE. (3) As the majority of women (all groups) breastfeed there is a need to continue vitamin D and calcium supplementation postnatally. (4) Our results suggest that prescribing vitamin D and calcium both to pregnant and breastfeeding women from ethnic populations should take place with or without screening. (5) A randomised controlled trial is needed to clarify both the indications and benefits of vitamin D and calcium supplementation to these populations. Abstract PM.13 Indications for ICU admission.